Efficacy and Safety of an Ophthalmic DMPC-Based Nanoemulsion in Patients with Dry Eye Disease: A Phase I/II Randomized Clinical Trial - Leopoldo M. Baiza-Durán; Patricia Muñoz-Villegas; Alejandra Sánchez-Ríos; Oscar Olvera-Montaño (Journal of Ophthalmology)
Purpose. The goals of this study were to evaluate the safety and efficacy of an ophthalmic 1,2-dimyristoyl-sn-glycero-3-phosphocholine (DMPC)-based nanoemulsion (Nanodrop®) in patients with dry eye disease (DED). Methods. This was a randomized phase I/II multicentric, prospective, double-blind clinical trial. Patients (phase I: n = 25 and phase II: n = 101) were assigned to receive either PRO-176 (Nanodrop®) or Systane Balance® (control) for 29 days. Once the visits of the first 25 subjects were completed, if there were less than 20% of unexpected adverse events (AEs), related to PRO-176, recruitment was continued until the sample was completed for noninferiority (efficacy) analysis (phase II, n = 126). Efficacy endpoints were the ocular surface disease index (OSDI), tear break-up time (TBUT), epithelial defects, best corrected visual acuity (BCVA), and the incidence of expected AE. Results. For the phase I portion of the study, there were no differences between groups regarding the incidence of AE. All related-AE symptoms in both groups were mild and expected. For the phase II subset, there was a significant reduction in OSDI scores at day 29 and noninferiority between treatments was confirmed (p=0.650, CI 95% [−8.7, 5.5]). Similar improvement was observed for TBUT although no significant intergroup differences were found (p=0.518, CI 95% [−0.08, 1.6]). There were no significant differences between treatments for epithelial staining or safety parameters. Conclusions. Topical application of PRO-176 is as safe and effective as the controls. Both groups were clinically similar in terms of efficacy and safety. The results support the hypothesis that ophthalmic DMPC-based nanoemulsion may improve clinical parameters and symptoms in patients with DED. This trial is registered with NCT04111965.